2014
DOI: 10.1111/vco.12116
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of treatment and response of high‐risk mast cell tumours in dogs

Abstract: This retrospective case series evaluates survival outcome of 94 dogs with high metastatic risk mast cell tumours (MCT). Patients were treated with a cytotoxic chemotherapy protocol or the tyrosine kinase inhibitor masitinib, in the presence of gross disease or as an adjunct to surgical resection of the primary tumour. In patients presenting with metastatic disease, surgical resection of the primary tumour with adjunctive therapy with any chemotherapy incurred a significant survival advantage [median survival t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 22 publications
6
71
1
4
Order By: Relevance
“…However, this finding was not noticed in this study, and was also not observed in the study by Miller et al (2014). In a study conducted by Michels et al (2002), the likelihood of recurrence in MCT with evidence of incomplete surgical margins was not higher than those with clean margins.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…However, this finding was not noticed in this study, and was also not observed in the study by Miller et al (2014). In a study conducted by Michels et al (2002), the likelihood of recurrence in MCT with evidence of incomplete surgical margins was not higher than those with clean margins.…”
Section: Discussioncontrasting
confidence: 44%
“…(Blackwood et al, 2012;London and Thamm, 2013;Miller et al, 2014) Patients at intermediate-risk (group B) were subdivided in three groups: B1, formed by patients treated with adjuvant vinblastine (Velban, ABL) at a dosage of 2 mg / m² every seven days, for four sessions, and then every 14 days for four more sessions followed by the eight-week chlorambucil protocol; B2, formed by patients treated with the eight-week protocol using chlorambucil; and B3 formed by patients whose owners declined any further treatment beyond surgery (intermediate-risk control).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metastasis prevention or delay is one of the main aims of adjuvant chemotherapy (Ogilvie 1998). Due to the risk of the development of metastatic disease in the aforementioned tumour types, adjuvant chemotherapy has been reported to reduce the risk of both local recurrence and further spread of these tumours (Moore and others 2007, Blacklock and others 2012, Miller and others 2014, Sharma and others 2014, Wendelburg and others 2015, Shorupski and others 2016). In one study, 70.8 per cent of general veterinary practitioners (GVPs) prescribed a cytotoxic drug for a canine or feline patient between November 2003 and November 2004 and, in the same period, 38.9 per cent of GVPs referred a patient to an oncologist for chemotherapy (Cave and others 2007).…”
mentioning
confidence: 99%